To solve the equation, we can distribute the numbers outside the parentheses to the terms inside:
6 * -8x + 6 * 7 = 7 * 5x + 7 * 6
-48x + 42 = 35x + 42
Now, we can get all the x terms on one side by subtracting 35x from both sides:
-48x + 42 - 35x = 35x + 42 - 35x
-83x + 42 = 42
Next, we can isolate the x term by subtracting 42 from both sides:
-83x + 42 - 42 = 42 - 42
-83x = 0
Finally, we can solve for x by dividing both sides by -83:
x = 0
Therefore, the solution to the equation is x = 0.
6(−8x+7)=
7(5x+6)
Answer
Attempt 3 out of 3
The equation has
one solution
and it is x, equalsx=
.
1 answer